2018
DOI: 10.1001/jamaophthalmol.2017.6658
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Retinopathy of Prematurity With Low Levels of Arachidonic Acid

Abstract: Key Points Question How are circulatory levels of ω-3 and ω-6 long-chain polyunsaturated fatty acids associated with retinopathy of prematurity? Findings In this secondary analysis of data from a randomized clinical trial of 78 infants, higher ω-6 polyunsaturated fatty acid arachidonic acid serum levels were associated with a lower risk of developing any retinopathy of prematurity, as well as sight-threatening retinopathy of prematurity. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 41 publications
2
61
2
Order By: Relevance
“…It is well-documented that in the early postnatal period of preterm infants, whole blood docosahexaenoic acid (DHA, C22:6n-3) and arachidonic acid (ARA, C20:4n-6) deficits and linoleic acid (LA, C18:2n-6) excesses occur within the first postnatal week [50]. Although these altered fatty acid profiles have been linked to the increased risk of developing bronchopulmonary dysplasia, retinopathy of prematurity, and late onset sepsis, the impact of these altered fatty acid profiles on intestinal development has just recently been described [50][51][52].…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…It is well-documented that in the early postnatal period of preterm infants, whole blood docosahexaenoic acid (DHA, C22:6n-3) and arachidonic acid (ARA, C20:4n-6) deficits and linoleic acid (LA, C18:2n-6) excesses occur within the first postnatal week [50]. Although these altered fatty acid profiles have been linked to the increased risk of developing bronchopulmonary dysplasia, retinopathy of prematurity, and late onset sepsis, the impact of these altered fatty acid profiles on intestinal development has just recently been described [50][51][52].…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…In premature infants, high triglycerides are associated with increased severity of retinopathy of prematurity (ROP; Sinclair et al , ). The ω‐6 LCPUFA, arachidonic acid, level is also significantly lower in severe ROP in premature infants at postmenstrual age of 32 weeks (Lofqvist et al , ). Although the results from many studies exploring the associations between diabetic retinopathy (DR) and lipid abnormality are inconsistent, one study found that high circulating LDL cholesterol levels are a significant risk factor for diabetic macular edema and retinal hard exudates (Chang & Wu, ).…”
Section: Dyslipidemia In Neurovascular Retinopathiesmentioning
confidence: 99%
“…Severe ROP is reduced in premature infants (GA < 32 weeks) receiving ω‐3 LCPUFA versus parenteral soybean and olive oil supplementation (Pawlik et al , ). There is also an association between low serum levels of ω‐6 LCPUFA (AA) and later development of ROP (Lofqvist et al , ). In mice, dietary ω‐3 versus ω‐6 LCPUFA suppresses retinal neovascularization (Connor et al , ; Fu et al , ).…”
Section: Dyslipidemia In Neurovascular Retinopathiesmentioning
confidence: 99%
“…Macronutrient transport protein expression has been associated with cellular-level placental histologic changes in preeclampsia; specifically, increased fatty acid placental transfer and maternal systemic circulation have been suggested to mediate disease in early onset preeclampsia [190]. As discussed previously, ROP development has been associated with decreased circulating fatty acids longitudinally from birth [191]. Combined, these studies suggest that an integrated systems approach, combining maternal and placental pathobiology relative to preterm infant ROP can elucidate underlying mechanisms of protection that can be therapeutically replicated post-natally or even in-utero to prevent ROP.…”
Section: A Novel Model Of Natural Rop Protectionmentioning
confidence: 99%